Response to influenza vaccination in immunocompromised children with rheumatic disease: a prospective cohort study - Lotte Jensen; Susan Nielsen; Anne Estmann Christensen; Freddy Karup Pedersen; Ramona Trebbien; Thea K Fischer; Susanne Rosthøj; Peter Toftedal; Anna-Helene Bohr; Peder Skov Wehner; Anja Poulsen (BMC, 2021)
Abstract Background Prevention of illness due to infection by influenza viruses is important for children with rheumatic diseases. Biological disease modifying antirheumatic drugs have become increasingly important in the treatment of juvenile idiopathic arthritis, and combinations of immunosuppressive drugs are used for the treatment of systemic disorders, which increase the risk of secondary immunodeficiency. Therefore, we investigated whether children with rheumatic disease can mount a protective antibody response after influenza immunization. Methods The prospective multicentre cohort study was conducted in Denmark during the influenza season 2015-2016. Children with rheumatic disease aged six months to 19 years were eligible. Controls were immunologically healthy children. A blood sample was collected before and after vaccination and analysed by haemagglutination inhibition (HI) assay for the 2015-2016 influenza vaccine-strains. In case of flu-like symptoms the child was tested for influenza. For statistical analyses the patients were grouped according to medical treatment or disease. Results A total of 226 patients and 15 controls were enrolled. No differences were found for the increase of antibodies from pre-vaccine to post-vaccine between the groups in our primary analyses: A/Cal H1N1pdm09 (p = 0.28), A/Swi H3N2 (p = 0.15) and B/Phu Yamagata (p = 0.08). Only when combining patients across groups a lower increase in antibodies was found compared to controls. Among all patients the pre-vaccine rates for seroprotection using the HI-titer cut-off ≥ 40 were 93.1-97.0 % for all three strains. For seroprotection using the HI-titer cut-off ≥ 110 the pre-vaccine rates for all patients were 14.9-43.6 % for all three strains and an increase in the proportions of patients being seroprotected after vaccination was found for A/Cal H1N1pdm09 and A/Swi H3N2. None of the children with flu-like symptoms tested positive for the vaccine strains. Conclusions Children with rheumatic diseases increase in antibody titres after influenza immunization, however, it remains uncertain whether a protective level is achieved.